PENGEMBANGAN MEDIA PEMBELAJARAN RIESENSCHLANGE UND LEITER UNTUK KETERAMPILAN BERBICARA BAHASA JERMAN SMA - Maharani, Funny; Pujosusanto, Ari (LATERNE, 2024)
This study developed the instructional media "Riesenschlange und Leiter" (Giant Snakes and Ladders) to enhance German-speaking skills among high school students using the ADDIE development model. The game was modified to a larger-than-normal size to facilitate use in classroom learning. The study was motivated by internal factors, such as students’ low learning motivation, lack of confidence, and passive behavior, as well as external factors, including limited innovation in teaching methods. Media development followed the five ADDIE phases (Analysis, Design, Development, Implementation, Evaluation) with research subjects comprising material and media experts as validators, and 36 eleventh-grade students from SMAN 1 Menganti. Data were collected through observations, expert feedback, and student questionnaires. Validation results indicated suitability ratings of 92.5% from media experts, 90% from material experts, and 92.2% from student responses. Based on qualitative and quantitative data, the Riesenschlange und Leiter media was found to be effective for enhancing speaking skills on the topic “Gegenstände in der Schule” for eleventh-grade students.